Expression of the Caenorhabditis elegans aryl hydrocarbon receptor ligand binding domain - Helaly, Ahmed (2011)
The Aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor, which mediates the potent toxic effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and related compounds. AhR is regulated by the ligand-binding domain (LBD) of the AhR, and so determining how the binding of ligand activates AhR is of considerable interest. However, there are no structural data on mammalian AhR LBDs, and expression of the mouse AhR LBD in E. coli yields insoluble protein. Expression in more complex systems, such as insect cells (Spodoptera frugiperda), yields soluble AhR LBD, but only ~10% of the total protein is in a ligand-binding competent form. In order to address the structure of the AhR LBD, we have used a model system. There is good amino acid sequence similarity between human AhR and C. elegans AhR (CeAhR). We have investigated whether the three dimensional structure of CeAhR LBD will help in understanding this structure in mammals. CeAhR LBD was cloned into the vector pRSET to give histidine-tagged protein. The clones were then transformed into E. coli BL21(DE3) or Arctic Express strains, followed by induction with IPTG. Bacteria were lysed and 100000g supernatants were prepared. Proteins were purified by Ni2+ affinity chromatography. Expression of recombinant proteins in the bacterial system revealed that the induced protein from the pRSET.CeAhR LBD construct was ~29 kDa, as predicted. Large amounts of these proteins were produced (~5-10% of total bacterial protein) and the vast majority was insoluble. However, on preparation of a 100000g supernatant, the samples yielded small amounts of soluble CeAhR LBD fusion protein. This is in contrast to results obtained with mouse AhR LBD, which yielded no detectable protein in a 100000g supernatant. The CeAhR LBD proteins were successfully purified by affinity chromatography and were obtained in good yield from the original cytosols. However, the yield of soluble AhR fusion protein was ~100 microgrammes of protein per litre of BL21(DE3) bacterial culture. The experiment was repeated using Arctic Express bacteria, which have a constitutively expressed chaperonin, and express at 12°C. However, the yield of protein was similar, at ~100 microgrammes of protein per litre. Thus the CeAhR LBD yields soluble protein in a bacterial expression system, but the levels of expression are too low to enable this protein to be purified for use in structural studies. Trials to express CeAhR LBD in transgenic C. elegans and Pichia pastoris yielded no soluble protein. The research moved to look for ligands for CeAhR by using a lethality test with C. elegans in vivo studies. The results showed that TCDD and AZ1c (from AstraZeneca) affect the wild type C. elegans, but without killing them. Repeating this test on AhR null animals showed that the effects were abolished. Thus the CeAhR is a receptor that appears to bind TCDD and AZ1c, albeit weakly, contrary to previous reports in the literature.